STUDY OF EFFICACY AND TOXICITY OF HYPOFRACTIONATED THORACIC RADIOTHERAPY 17 GRAY IN 2 FRACTIONS FOR PALLIATION IN ADVANCED NON-SMALL-CELL LUNG CANCER: Palliation in Advanced Non-Small-Cell Lung Cancer - Arif, Maj Salman; Rasul, Shahid Rasul; Haider, Naeem; Mahmood, Ahsan; Syed, Abdus Samad; Nadeem, Mohammad; Amin, Zulfiqar (Pakistan Armed Forces Medical Journal, 2012)
Objectives: To determine the efficacy and toxicity of hypofractionated thoracic radiotherapy 17 Gray (Gy) in 2 fractions for palliation in advanced non.small-cell lung carcinoma. Study design: A quasi-experimental study. Place and duration of study: Oncology department, Combined Military Hospital, Rawalpindi, from 4th July 2008 to 4th Nov 2009. Material and Methods: Fifty four patients with histologically and/or cytologically confirmed unresectable stages III and IV non small cell lung cancer, with performance status 2 or 3 and expected survival . 2 months were treated with megavoltage radiation therapy 17 Gy in 2 fractions one week apart, with symptoms due to intrathoracic disease (cough, dyspnea and hemoptysis) and toxicity due to radiation therapy (dysphagia secondary to esophagitis) assessed as per common toxicity criteria adverse event version 3.0 on day 0 before treatment and day 30 after start of treatment. Results: Grades of cough, hemoptysis and dyspnea showed significant improvement after treatment (p<0.001). A total of 42.68% patients showed an improvement in grade of cough (23 out of 54 patients), 85.7% of patients showed improvement in grade of hemoptysis (36 out of 42 patients) and 55.65% patients showed improvement in grade of dyspnea (30 out of 54 patients). Twenty two point two percent patients (12 out of 54) showed increase in grade of dysphagia. Although, there was a statistically significant increase in grade of dysphagia after treatment but it was limited to grade 1 and 2 only. Considering that no patient had grade 3 or 4 dysphagia, this toxicity was acceptable. Conclusion: Based on our results hypofractionated thoracic radiotherapy, 17 Gy in 2 fractions, is effective with acceptable toxicity in palliation in advanced non small cell lung cancer and is recommended as it will result in shorter duration of hospital stay and low hospital stay charges.